Reading fluency as the bridge between decoding and reading comprehension in Chinese children - Hsu, Lucy Shih-Ju; Chan, Kevin; Ho, Connie Suk-Han (Frontiers in Psychology, 2023)
Purpose: Reading fluency has been considered an essential component of reading comprehension, but it has yet to be examined in a reading model in a non-alphabetic writing system. This work investigated whether reading fluency could be identified as a separate construct from decoding and examined the unique role of reading fluency in the Simple View of Reading (SVR). Method: A total of 342 grades 3 to 5 Cantonese-speaking Chinese children were recruited to participate in the study. They were assessed on word reading accuracy and fluency, morphological awareness, vocabulary knowledge, and reading comprehension. Results: The confirmatory factor analysis results confirmed that reading fluency is a separate factor from decoding, linguistic comprehension, and reading comprehension. Furthermore, the structural equation modeling results revealed that reading fluency is a significant predictor of reading comprehension and a mediator between decoding and reading comprehension in the extended SVR model. Conclusion: The findings extended previous research in alphabetic languages and supported reading fluency as the bridge between decoding and reading comprehension. The present work highlighted the importance of reading fluency in Chinese reading acquisition in a theoretical framework.